The SERC Report: Projecting an Absence of Conceptual Clarity - Colgan, Anne (REACH: Journal of Inclusive Education in Ireland, 1994)
It may be argued that the various terms relating to children's special needs, the role of parents and the structures of educational arrangements, were applied loosely rather than definitionally in the Report. However, since they are drawn on to relate levels of need to placement along the continuum of educational options, then their inconsistency creates significant difficulty for those attempting to identify the overall shape of the proposed service provision.